Predicting throwing performance with field tests - Zaras, N.; Stasinaki, A.-N.; Arnaoutis, G.; Terzis, G. (New Studies in Athletics, 2016)
The purpose of this study was to investigate whether training-induced changes in muscle power evaluated with easy-to-use field tests are linked with performance in the shot put, discus, hammer and javelin after long-term training. Ten well-trained throwers participated in a 20-week training programme for winter competition. Measurements taken before and after the programme included competitive shot put throws, seated medicine ball throws, standing long jump, 30m sprint, countermovement jumps on a force platform with various loads, and body composition analysis. Significant increases were observed for competition throwing performance and for most of the power tests (P < 0.05). Significant correlations were found between the training-induced increases in competition throws and the increase in performance in the shot put tests (r = 0.68-0.76, P < 0.05), as well as in the seated medicine ball throw (r - 0.89, P = 0.004). The results of the study suggest that increases in muscle power measured with easy-to-use field tests may predict the increases in competition throwing performance anticipated with long-term training and therefore that these tests can be useful for coaches without regular access to laboratory testing.